Ownership concentration and bank risk (A study on banking sectors in Indonesia) - Etikah Karyani; Sidharta Utama (Universitas Hayam Wuruk Perbanas, 2015)
The purpose of this study is to test empirically the relationship between ownership concentration and risk taking by banks which are proxied by the CAR and LDR (li-quidity ratio). The study was motivated by the limited previous studies that analyze the structure of ownership in financial institutions and the weaknesses in sampling. Our analysis focused on Indonesia because this country has implemented the Basel Accord II standards successfully. This regulatory compliance is expected can control banking risk. Using data from 2009 until 2013 and panel data. We found that the ownership concentration become important determinants of bank liquidity. These findings are expected to provide policy guidance for regulators, especially relating to the ownership structure of the bank. However, the ownership concentration proved to be involved in the management decision to risk taking in banks.